Hubungan Pengetahuan dan Perilaku tentang Vulva Hygiene Terhadap Keputihan - Siti Khoriyah; Ice Khodijah (Lembaga Pengembangan Kinerja Dosen, 2024)
Fluor albus is one of the symptoms. Incidence of STDs and other reproductive diseases is often not reported because patients feel ashamed, afraid and anxious. Fluor albus, this is normal for women but it's still annoying to experience a lot of discomfort, vaginal discharge in Indonesia is 90% because Indonesia has a tropical climate, fungi grow easily and there is a lot of vaginal discharge in Indonesian women. This type of research is descriptive correlation with cross sectional design. The population in this study were all 30 female students/adolescents. The sample used a total sampling technique so that the number of respondents used was the same as the population, namely as many as 30 female students. The data collected is primary data, namely questionnaires filled out directly by junior high school student respondents in 2023. The results of the vaginal discharge study found that 20 people (6.7%) did not experience vaginal discharge, while 28 people (93.3%) experience vaginal discharge. Student knowledge about vulva hygiene, namely from 30 respondents who had good knowledge as many as 5 respondents (16.7%), who had sufficient knowledge as many as 5 respondents (16.7%), who had less knowledge as many as 20 respondents (66.6%). Student behavior regarding vulva hygiene, namely from 30 respondents who behaved well as many as 7 respondents (23.3%), who behaved quite well as many as 6 respondents (20.0%), who behaved poorly as many as 17 respondents (56.7%). Using the Chi square test it showed that there was a relationship between knowledge of vulva hygiene and the incidence of vaginal discharge (p value = 0.012) and showed that there was a relationship between vulvar hygiene behavior and the incidence of vaginal discharge (p value = 0.000). The conclusion of this study is that there is a relationship between knowledge and behavior regarding vulva hygiene and vaginal discharge.